Specific and promiscuous ophiostomatalean fungi associated with Platypodinae ambrosia beetles in the southeastern United States. (October 2018) - Li, You; Huang, Yin-Tse; Kasson, Matthew T.; Macias, Angie M.; Skelton, James; Carlson, Paige S.; Yin, Mingliang; Hulcr, Jiri
Abstract: Ambrosia beetles in the subfamily Platypodinae (Coleoptera: Curculionidae) have been farming fungi for over 50 million y, yet they remain understudied and most of their fungal symbionts are unknown. We identified fungal communities associated with all four platypodine species native to the southeastern United States: Euplatypus compositus, Euplatypus parallelus, Myoplatypus flavicornis, and Oxoplatypus quadridentatus . Forty-eight samples were analyzed by quantitative culturing and DNA sequencing. Phylogenetic analyses of 28S rDNA sequences revealed that the four platypodines were routinely associated with several genera in the Ophiostomatales. E. compositus is associated primarily with Raffaelea campbellii 1 and Raffaelea sp. 6 and, to a lesser extent, Raffaelea sp. 2. M. flavicornis is associated with Raffaelea sp. 5. E. parallelus and O. quadridentatus are less specific; the latter mostly associated with Raffaelea cyclorhipidia . Three of the four beetle species were also associated with Ceratocystiopsis spp. This is the first report of Raffaelea associated with E. parallelus, which is invasive in Asia and Africa.